Theology and practice of Christ Apostolic Church on Bible inspiration and its authority in the context of Evangelical theology - Folarin, George O. (HTS teologiese studies, 2018)
The motivation for this study originated from a review of literature which led the current researcher to the realisation that not much critical study has been performed on the theology and practice of Bible inspiration and its authority in Christ Apostolic Church (CAC). This article set out to identify the tenet of faith of the church on inspiration and authority of the Scriptures, locate this tenet in the context of Evangelical theology and compare the initial understanding of the concept of Bible inspiration in CAC with the way it is perceived by the church members today. Primary sources of data for the work comprised the Bible, editions of CAC constitution and structured interviews. Secondary sources of data comprised Bible commentaries, books, journal articles and the Internet. Data collected were analysed using Conservative Evangelical theological framework. The study discovered that CAC held to word-for-word inerrancy of the Scriptures, even of its vernacular translations, and its binding authority on Christians in all areas of their lives. The study revealed that the belief of CAC on Bible inspiration and its authority located CAC at the centre of Evangelical theology which researchers have identified as inerrancy. Finally, the study discovered that the initial position of CAC on the inspiration and authority of the Bible remained the same as held by contemporary members of the church. The work provides theological relevance for the study of one of the doctrines of Pentecostalism in Nigeria.